Intrinsic connectivity networks from childhood to late adolescence: Effects of age and sex. (February 2016) - Solé-Padullés, Cristina; Castro-Fornieles, Josefina; de la Serna, Elena; Calvo, Rosa; Baeza, Inmaculada; Moya, Jaime; Lázaro, Luisa; Rosa, Mireia; Bargalló, Nuria; Sugranyes, Gisela
Highlights: We assessed intrinsic connectivity of networks underlying cognition in youth. Evidence of age effects on intrinsic connectivity was found across all networks. Intrinsic connectivity showed no effect of sex, nor age by sex interactions. Abstract: There is limited evidence on the effects of age and sex on intrinsic connectivity of networks underlying cognition during childhood and adolescence. Independent component analysis was conducted in 113 subjects aged 7–18; the default mode, executive control, anterior salience, basal ganglia, language and visuospatial networks were identified. The effect of age was examined with multiple regression, while sex and 'age × sex' interactions were assessed by dividing the sample according to age (7–12 and 13–18 years). As age increased, connectivity in the dorsal and ventral default mode network became more anterior and posterior, respectively, while in the executive control network, connectivity increased within frontoparietal regions. The basal ganglia network showed increased engagement of striatum, thalami and precuneus. The anterior salience network showed greater connectivity in frontal areas and anterior cingulate, and less connectivity of orbitofrontal, middle cingulate and temporoparietal regions. The language network presented increased connectivity of inferior frontal and decreased connectivity within the right middle frontal and left inferior parietal cortices. The visuospatial network showed greater engagement of inferior parietal and frontal cortices. No effect of sex, nor age by sex interactions was observed. These findings provide evidence of strengthening of cortico-cortical and cortico-subcortical networks across childhood and adolescence.